Calvarial involvement in disseminated rhinosporidiosis – A case report and literature review - Dewangan, B (J Postgrad Med, 2020)
Rhinosporidiosis is a chronic granulomatous infection caused by Rhinosporidium seeberi and mainly involves nasal and ocular mucosa. Bony involvement in rhinosporidiosis is very rare. A young male, previously operated for nasal rhinosporidiosis, presented with two bony swellings on the forehead and multiple subcutaneous lesions on the right lower limb. The diagnosis of disseminated cutaneous rhinosporidiosis with frontal bone involvement was made with the help of fine needle aspiration cytology (FNAC), histopathology, and computed tomography (CT) scan head. Wide excision of the bony lesion was performed. To the best of our knowledge, this is the first radiologically proven case of frontal bone involvement in disseminated rhinosporidiosis. Early diagnosis can be established with a good clinicopathological and radiological correlation. It also emphasizes the importance of CT scan for the evaluation of any subcutaneous skull lesion.